Participation Intensity Influences Motivations for Contributing to iNaturalist - Lowe, Samantha K.; Mason, Brittany M.; Guralnick, Robert; Morales, Nia A.; Callaghan, Corey T. (Citizen science : theory and practice, 2025)
Understanding how motivations for participating in citizen science projects change as a function of participation can help enhance recruitment and retention strategies. Previous studies indicate that motivations focused on science and conservation often become more important over time, while egoistic motivations tend to decline in importance. Here, we investigate how participant motivations change as a function of participation level by surveying users of the citizen science platform iNaturalist. We surveyed 429 iNaturalist users using a combination of quota and convenience sampling methods. Participants rated the importance of 15 motivations on a five-point Likert-type scale and provided their total number of contributions to iNaturalist, allowing us to analyze how the importance of motivations varied with participation intensity. Our findings revealed that learning-oriented motivations, specifically improving species knowledge and discovering information about ecosystems, consistently ranked as the most critical motivations regardless of participation intensity. Science and conservation motivations gained importance with increased observation counts but did not surpass learning motivations. Contrary to prior findings, egoistic motivations either maintained or increased in significance at higher participation levels. These insights into iNaturalist users’ motivations suggest the potential need for tailored engagement strategies that account for learning and curiosity-driven participation in citizen science.